Modeling of Thermal Effects in Semiconductor Structures. Issue 1 (1998) - Snowden, Christopher M.
Abstract : A fully coupled electro-thermal hydrodynamic model is described which is suitable for modelling active devices. The model is applied to the non-isothermal simulation of pseudomorphic high electron mobility transistors (pHEMTs). A large-scale surface temperature model is described which allows thermal modelling of semiconductor devices and monolithic circuits. An example of the application of thermal modelling to monolithic circuit characterization is given.